Subtle subversions: reading Golden Age sonnets by Iberian women - Fox, Gwyn (Catholic University of America Press, 2008)
Introduction : Revisiting the Baroque -- Politics, patronage, parentage -- Marriage, motherhood, patriarchy -- Children and siblings -- Feminine friendship -- Women's love sonnets -- Luisa de Carvajal : more Martha than Mary -- Conclusion : Living the Baroque